A microcomputer implementation of PLA function and its use in a laboratory dealing with arithmetic algorithms - Abe, K.; Naraoka, M.; Wakatsuki, Y. (IEEE transactions on education, 1989)
The function of a programmable logic array (PLA) was implemented using a microcomputer. The equipment is suitable for use in laboratories because it is electrically programmable, easy to be realized and maintained, and has sufficient capacity. It has been used for implementing fixed-point arithmetic algorithms, a subject of a laboratory course given to computer science majors of the University of Electro-Communications. The PLA program is created on a personal computer using a text editor and transmitted to the PLA through a serial communication line. Parallel interface circuits between the personal computer and the arithmetic unit to be implemented by the students were also prepared. The arrangements enable them to write and execute Pascal programs to test whether the implementation meets given specifications.< >